Pertumbuhan Bibit Sengon (Paraserianthes falcataria (L) Nielsen) pada Media Bekas Tambang Pasir dengan Pemberian Subsoil dan Arang Tempurung Kelapa - Basuki Wasis; Nur Syarif (Jurnal Silvikultur Tropika, 2019)
Mining sand river continously is likely to decrease sand stock and to damage soil and its environment. The application of adding subsoil and coconut shell charcoal propitiously can help recover tailling l for sengon seedling crop media. The purpose is to identify the effects of adding subsoil and coconut shell charcoal for the growth of sengon seedling. Research method used are factorial trial design with two factors of which four-step subsoil factor A (0 gram, 250 gram, 500 gram and 750 gram) and ccoconut shell charcoal(0 gram, 20 gram, 40 gram, and 60 gram) with 3 repetitions. The treatment of coconut shell charcoal and subsoil significantly affected all observed parameters, namely plant height, diameter, total wet weight, and total dry weight.. Treatment of 75% subsoil and charcoal 60 g (A3B3) is the best treatment.  Key words: coconut shell charcoal, sand mining, Sengon, sub soil, sand mining